Impact of antipsoriatic therapy on endothelial function. (1st November 2015) - Cohen‐Barak, E.; Sah, M.; Kerner, M.; Rozenman, D.; Ziv, M.
Summary: Background: Endothelial function (EF) impairment is one of the first events in the process of atherosclerosis, which is known to be associated with psoriasis. Nevertheless, the effect of antipsoriatic treatments, some of them with atherogenic risks, on cardiovascular morbidity and EF is still unclear. Objectives: To investigate the effect of short‐term antipsoriatic treatments on EF values as a potential marker of their effect on cardiovascular morbidity. Methods: EF was evaluated in 26 patients with moderate‐to‐severe psoriasis by measuring microvascular blood flow, expressed as the reactive hyperaemia index (RHI), before and after phototherapy (8 weeks) or systemic antipsoriatic treatment (12 weeks). Results: Antipsoriatic intervention was effective (46% achieving ≥ 75% improvement in Psoriasis Area and Severity Index), while the average RHI did not improve during the study (1·73 ± 0·48. vs. 1·66 ± 0·35, average difference −0·12 ± 0·43, not significant). Patients with baseline preserved EF exhibited a decline in RHI (difference −0·2 ± 0·4, P = 0·053), while patients with abnormal baseline RHI presented nonsignificant RHI improvement (RHI difference 0·1 ± 0·2). Conclusions: There was no positive effect on EF of short‐term antipsoriatic treatment. It is possible that a longer period of treatment and EF evaluation would uncover a positive endothelial effect, especially in patients with baseline abnormal EF. Abstract : What's already known about this topic? Psoriasis was recently associated with cardiovascular morbidity. The effect of antipsoriatic treatment on cardiovascular morbidity remains obscure. Endothelial function (EF) impairment is an early event in cardiovascular morbidity, and is used as a marker for it. What does this study add? Short‐term antipsoriatic treatments failed to improve EF. EF worsened in patients whose baseline value was preserved, probably due to the atherogenic effect of some of the treatments. Linked Comment: Egeberg, Br J Dermatol 2015; 173: 1362–63 .